Wyndham Cemetery 1881-2004 - Ryan-Taylor, Nardia ([Lakes Entrance, Vic.] : N. Ryan-Taylor, 2004)
Monumental inscriptions with photos.
Title from disc.
System requirements: Windows 98 or higher; 64mb RAM; 24x CD ROM drive; Internet Explorer or Netscape Navigator.
Keywords: Wyndham Cemetery (N.S.W.); Cemeteries -- New South Wales -- Wyndham; Wyndham (N.S.W.) -- Genealogy